Gas-assisted silver deposition with a focused electron beam - Berger, Luisa; Madajska, Katarzyna; Szymanska, Iwona B.; Höflich, Katja; Polyakov, Mikhail N.; Jurczyk, Jakub; Guerra-Nuñez, Carlos; Utke, Ivo (Beilstein Journal of Nanotechnology, 2018)
Focused electron beam induced deposition (FEBID) is a flexible direct-write method to obtain defined structures with a high lateral resolution. In order to use this technique in application fields such as plasmonics, suitable precursors which allow the deposition of desired materials have to be identified. Well known for its plasmonic properties, silver represents an interesting candidate for FEBID. For this purpose the carboxylate complex silver(I) pentafluoropropionate (AgO2CC2F5) was used for the first time in FEBID and resulted in deposits with high silver content of up to 76 atom %. As verified by TEM investigations, the deposited material is composed of pure silver crystallites in a carbon matrix. It showed good electrical properties and a strong Raman signal enhancement. Interestingly, silver crystal growth presents a strong dependency on electron dose and precursor refreshment.
Keywords: focused electron beam induced deposition; low volatility precursor; silver

(untitled) - Hari, S.; Hagen, C. W.; Verduin, T.; Kruit, P. (J. Micro/Nanolithogr., MEMS, MOEMS, 2014)

(untitled) - Scotuzzi, M.; Kamerbeek, M. J.; Goodyear, A.; Cooke, M.; Hagen, C. W. (Proc. SPIE, 2015)

(untitled) - Van Dorp, W. F.; Beyer, A.; Mainka, M.; Gölzhäuser, A.; Hansen, T. W.; Wagner, J. B.; Hagen, C. W.; De Hosson, J. T. M. (Nanotechnology, 2013)

(untitled) - Fowlkes, J. D.; Winkler, R.; Lewis, B. B.; Stanford, M. G.; Plank, H.; Rack, P. D. (ACS Nano, 2016)

(untitled) - Jesse, S.; Borisevich, A. Y.; Fowlkes, J. D.; Lupini, A. R.; Rack, P. D.; Unocic, R. R.; Sumpter, B. G.; Kalinin, S. V.; Belianinov, A.; Ovchinnikova, O. S. (ACS Nano, 2016)

(untitled) - Wnuk, J. D.; Rosenberg, S. G.; Gorham, J. M.; van Dorp, W. F.; Hagen, C. W.; Fairbrother, D. H. (Surf. Sci., 2011)

(untitled) - Utke, I.; Hoffmann, P.; Melngailis, J. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.--Process., Meas., Phenom., 2008)

(untitled) - Schuller, J. A.; Barnard, E. S.; Cai, W.; Jun, Y. C.; White, J. S.; Brongersma, M. L. (Nat. Mater., 2010)

(untitled) - Höflich, K.; Becker, M.; Leuchs, G.; Christiansen, S. (Nanotechnology, 2012)

(untitled) - Winkler, R.; Schmidt, F.-P.; Haselmann, U.; Fowlkes, J. D.; Lewis, B. B.; Kothleitner, G.; Rack, P. D.; Plank, H. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - van Dorp, W. F.; Hagen, C. W. (J. Appl. Phys., 2008)

(untitled) - Utke, I.; Gölzhäuser, A. (Angew. Chem., Int. Ed., 2010)

(untitled) - Höflich, K.; Jurczyk, J.; Zhang, Y.; Puydinger dos Santos, M. V.; Götz, M.; Guerra-Nuñez, C.; Best, J. P.; Kapusta, C.; Utke, I. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Bresin, M.; Nehru, N.; Hastings, J. T. (Proc. SPIE, 2013)

(untitled) - Fisher, J. S.; Kottke, P. A.; Kim, S.; Fedorov, A. G. (Nano Lett., 2015)

(untitled) - Szłyk, E.; Piszczek, P.; Grodzicki, A.; Chaberski, M.; Goliński, A.; Szatkowski, J.; Błaszczyk, T. (Chem. Vap. Deposition, 2001)

(untitled) - Szłyk, E.; Łakomska, I.; Grodzicki, A. (Thermochim. Acta, 1993)

(untitled) - Szymańska, I. B. (Polyhedron, 2013)

(untitled) - Kunz, R. R.; Mayer, T. M. (J. Vac. Sci. Technol., B: Microelectron. Process. Phenom., 1988)

(untitled) - Lukasczyk, T.; Schirmer, M.; Steinrück, H.-P.; Marbach, H. (Small, 2008)

(untitled) - Fernández-Pacheco, A.; De Teresa, J. M.; Córdoba, R.; Ibarra, M. R. (J. Phys. D: Appl. Phys., 2009)

(untitled) - Endrino, J. L.; Horwat, D.; Gago, R.; Andersson, J.; Liu, Y. S.; Guo, J.; Anders, A. (Solid State Sci., 2009)

(untitled) - Ferrari, A. C. (Solid State Commun., 2007)

(untitled) - Stamplecoskie, K. G.; Scaiano, J. C.; Tiwari, V. S.; Anis, H. (J. Phys. Chem. C, 2011)